2013
DOI: 10.1038/aps.2013.105
|View full text |Cite
|
Sign up to set email alerts
|

3D-QSAR and 3D-QSSR studies of thieno[2,3-d]pyrimidin-4-yl hydrazone analogues as CDK4 inhibitors by CoMFA analysis

Abstract: These two models provide useful information to guide drug design strategies aimed at obtaining potent and selective CDK4 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Obviously, these results provide valuable information for the design of a potential CDK4 inhibitor. Indeed, the production of statistically reliable 3D-QSAR (threedimensional quantitative structure-activity relationship) and 3D-QSSR (three-dimensional quantitative structure selectivity relationship) models derived from TP-4-yl hydrazone analogues (48 samples) as determined by CoMFA analysis has also been reported[75]. CoMFA (comparative molecular field analysis) contour maps that were in good agreement with the…”
mentioning
confidence: 75%
“…Obviously, these results provide valuable information for the design of a potential CDK4 inhibitor. Indeed, the production of statistically reliable 3D-QSAR (threedimensional quantitative structure-activity relationship) and 3D-QSSR (three-dimensional quantitative structure selectivity relationship) models derived from TP-4-yl hydrazone analogues (48 samples) as determined by CoMFA analysis has also been reported[75]. CoMFA (comparative molecular field analysis) contour maps that were in good agreement with the…”
mentioning
confidence: 75%
“…Thirty-two compounds in the test set were selected randomly and included compounds with a uniformly distributed range of pIC 50 values from 3.336 to 6.658, covering more than 3 log units, which is fit for 3D QSAR studies [ 26 ]. The conformation of the most active compound, 79 , was selected as a template structure to sketch the rest of the molecules [ 27 ]. The complete dataset (1–132) taken for study is shown in Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Potential CDK4 inhibitors can be designed by taking these preliminary results in consideration from obtained results. Indeed, the production of statistically reliable 3D‐QSAR (three‐dimensional quantitative structure activity relationship) and 3D‐QSSR (three‐dimensional quantitative structure selectivity relationship) models derived from TP‐4‐yl hydrazone analogs (48 samples) as determined by CoMFA analysis has also been reported .…”
Section: Tyrosine Kinasesmentioning
confidence: 99%